2002
DOI: 10.1021/ol025728u
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Diethylzinc Addition to Imines Employing Readily Available N-Monosubstituted Amino Alcohols

Abstract: An easily accessible chiral ligand 3c, which promoted diethylzinc addition to imines with 96-98% ee, has been found by finely screening N,N-disubstituted and N-monosubstituted amino alcohols. N-monosubstituted amino alcohols, on average, gave slightly higher enantioselectivities than their N,N-disubstituted analogues. These results imply that the restricted and rigid structure of amino alcohol is not the absolute requirement for the highly enantioselective dialkylzinc addition to diphenylphosphinoylimines. [st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Analogous to the work of the Soai group, a large library of 1,2-amino-alcohols, as well as oxazolines, has been examined by Gong, Mi, and coworkers ( Figure 3). 56,57,58,59 While the authors identified ligands 95, 96, and 97 as those which afforded the highest yields and enantioselectivities in these studies, these compounds offer only modest improvements over the previous ligands (vide supra).…”
Section: Scheme 36mentioning
confidence: 97%
“…Analogous to the work of the Soai group, a large library of 1,2-amino-alcohols, as well as oxazolines, has been examined by Gong, Mi, and coworkers ( Figure 3). 56,57,58,59 While the authors identified ligands 95, 96, and 97 as those which afforded the highest yields and enantioselectivities in these studies, these compounds offer only modest improvements over the previous ligands (vide supra).…”
Section: Scheme 36mentioning
confidence: 97%
“…This has been a limitation not only in diorganozinc addition chemistry (20)(21)(22)(23)(24)(25), but also in catalytic asymmetric nitro-Mannich (26), Mannich (27), and Strecker (28) processes that use similar electrophilic precursors. This inherent limitation is also present in the preparation of N-acylimines, and several strategies have been developed to circumvent this problem.…”
mentioning
confidence: 99%
“…It had been reported that N ‐monosubstituted amino alcohols exhibited slightly higher enantioselectivities than their N , N ‐disubstituted congener 4b. c Although 1 was successfully employed for the addition of dialkylzinc to imines with high enantioselectivity, we surveyed the N ‐monosubstituted amino alcohols 2 a–i for the feasibility of promoting the enantioselective addition reaction.…”
Section: Resultsmentioning
confidence: 99%